Human papillomavirus infection-related cancer risk for kidney transplant recipients during adult life can be reduced by vaccination during childhood and adolescence - Nailescu, Corina; Shew, Marcia L. (Frontiers in Pediatrics, 2022)
Malignancies are found between the first three reasons of mortality in pediatric and adult kidney transplant recipients, who overall have disproportionately higher rates of cancer compared to the general population, including human papillomavirus (HPV)-related genital, anal and oropharynx region cancers. Therefore, preventing HPV in this patient population is extremely important. HPV-vaccine was demonstrated to prevent HPV infection in individuals with intact immune systems. In addition, recent data reported less precancerous HPV lesions and cervical cancers with use of HPV vaccine. Since HPV is a sexually transmitted virus that is typically acquired shortly after the onset of sexual activity, it is best to administer the HPV vaccine immunization prior to the onset of sexual activity. This article reviews the epidemiology and pathophysiology of the HPV infection, as well as its role in the development of HPV-related pre-cancerous lesions and cancers in both general population and kidney transplant recipients. The focus is on the most effective primary prophylactic strategy, which is the HPV vaccination. The particularities of HPV vaccination strategies in kidney transplant recipients are compared to the general population. In addition, the article analyzes the various causes of suboptimal HPV immunization rates in kidney transplant candidates and recipients and discusses vaccination optimization strategies that can be applied during childhood and adolescence to reduce the burden of HPV-related disease states and cancer among adult kidney transplant recipients.